The importance of the use of technology in a virtual learning environment. - Alvarenga Hernández, Kenia Yasmin; Ramos Mejía, Marlyn Larissa; Mejía Cartagena, Leidi Esmeralda (2024)
Technology nowadays is one of the main reasons why teachers, students, and others can be introduced in a digital age that is delivering the future of education. This fact helps to improve and empower education through the benefits and facilities it offers. Thus, in a digital age, virtual environments for learning and teaching are an essential part of the process of improving virtual education. Hence, the principal objective of the specialization is that students have plenty of views and experience with virtual environments and what their terms imply in learning and teaching. Thus, it is vital to mention that the present report gives information on how this specialization is developed and what includes around it, moreover, they put into practice and produce what they acquire as well. Getting familiar and being enrolled in the course is enriching knowledge for the student because they have the option of learning and teaching not only face to face. Before the pandemic covid-19, at the University of El Salvador using virtual environments as a tool for teaching and learning was almost unknown to students. Hence, it is necessary to take into consideration getting involved in virtual environments to develop innovative classes. It can be said that specialization transforms the traditional expectations of learning and teaching nowadays. Key words: Technology; Virtual classroom; Educational platforms; Teaching-learning; Resources.